Produktivitas Kopi Arabika (Coffea arabica Linden.) pada Penaung Berbeda di Hutan Lindung Desa Sukalaksana Kabupaten Garut - Wilujeng, Sri; Darliana, Ina; Safari, Syahrul (Jurnal Agro Industri Perkebunan, 2024)
The protected forest area managed by Perum Perhutani in Sukalaksana village is dominated by pine trees (Pinus merkusii) and rasamala trees (Altingia excelsa). Coffee farmers in Sukalaksana village grow arabica coffee using an agroforestry system under pine and rasamala stands within the framework of joint forest management. So that the arabica coffee commodity can have optimal economic value, coffee farmers in Sukalaksana village need to observe the productivity of arabica coffee plants. The research location is in the protected forest area of Sukalaksana village, Talegong district, Garut Regency. The object of observation was the soil in coffee plantations, Timtim varieties of arabica coffee plants, planted using an agroforestry system with rasamala trees and pine trees as shade. Data were analyzed descriptively using an uncorrelated t-test and linear regression analysis. Descriptively, there is no difference in the fertility level of coffee planting soil on land shaded by rasamala and land shaded by pine. The productivity of coffee plants under the rasamala shade is higher than that of coffee plants under the pine shade. This is caused by significant differences in the branch-free bole height of shade trees. The rasamala shade has its first crown branch, which is higher than the pine shade.